Reforming Indonesian Government Bureaucracy: Political and Statutory Challenges in Reorganisation - Wijaya, Mas Pungky Hendra (Curtin University, 2020)
This thesis examines the governance structure of bureaucracy reform in Indonesia, particularly in the area of organisational changes, and investigates the extent to which political and statutory aspects influence and constrain reorganisation. It argues that successful reform is dependent on the capability to overcome political and statutory challenges of reorganisation. This thesis proposes a new legislative framework to support reorganisation that takes into account the current statutory framework and legal culture in reorganisation.